PENERAPAN KONSEP NARATIF MELALUI VISUAL PADA FILM FIKSI “CAKHRA KALA” - I Komang Frederich Blessy; I Komang Arba Wirawan; I Nyoman Payuyasa (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
A narrative storytelling through audio visual that tells about the conflict of a new married couple. Narrative film with the concept of timeloop has uniqueness That means a looping scene that makes the main character could change each action. The concept of timeloop is still rarely used in the Indonesian Film Industry. Therefore, making the concept of timeloop can make a development for the film industry in Indonesia. The concept is packaged by combining a little culture about the elements of locality in the conflicts that occur in the patriarchal system in Bali. The patriarchal system places men as holders of power in the family. Some family life in Bali, which is the backbone is a woman. So narrative and visual will be applied in this writing. The creation of the fiction film